2015
DOI: 10.1093/intqhc/mzv010
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve cultural competency in health care for Indigenous peoples of Australia, New Zealand, Canada and the USA: a systematic review

Abstract: There is a lack of evidence from rigorous evaluations on the effectiveness of interventions for improving cultural competency in health care for Indigenous peoples. Future evaluations should employ more rigorous study designs and extend their measurement of outcomes beyond those relating to health professionals, to those relating to the health of Indigenous peoples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
90
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(102 citation statements)
references
References 30 publications
0
90
0
Order By: Relevance
“…Consistent with previous reviews, a small number of published evaluations of cultural competency interventions were identified in the peer review literature and their methodological quality was less than optimal [6,7]. No evaluation studies from Canada or New Zealand were identified, despite these countries having accredited cultural competence training programs [27,28].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Consistent with previous reviews, a small number of published evaluations of cultural competency interventions were identified in the peer review literature and their methodological quality was less than optimal [6,7]. No evaluation studies from Canada or New Zealand were identified, despite these countries having accredited cultural competence training programs [27,28].…”
Section: Discussionmentioning
confidence: 83%
“…Although these requirements ensure that cultural competency is included in health and medical curricula, there is variation between health and medical schools in the content and delivery of this training [2,5]. Several reviews have examined the effects of cultural competence interventions on trained health professionals [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…as natural comparators in terms of Indigenous well-being..." because "these countries consistently place near the top of the United Nations Development Programme's Human Development Index (HDI) rankings, yet all have minority Indigenous populations with much poorer health and social conditions than their non-Indigenous compatriots". Various studies have compared some or all of these nations when examining Indigenous issues, including: social determinants of health [23]; rural food security [24]; culturally-competent health care practices [25]; lack of Indigenous participation in health research [26]; and disproportionate rates of urban homelessness for Indigenous peoples [27], yet there has not been a review of urban Indigenous food security that compares Indigenous experiences in Canada, the United States, and Australia. The Indigenous populations living in these three settler states face many of the same structural social, economic, and political inequalities that make them disproportionately vulnerable to food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of the present article is to offer a pragmatic approach, based on personal experiences in cross-cultural research, [7][8][9][10] by sharing some tips, anecdotes, and the eventual impact on public events. Hopefully some of these personal hints might serve professionals and other readers interested in promoting a better dialogue between different cultures thus going a little way towards solving conflicts, preventing violence, and achieving peace through tolerance.…”
mentioning
confidence: 99%